Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Precision forestry in actively managed loblolly pine plantations: Leaf area index response one growing season following a variable-rate fertilization - Chris W. Cohrs; Al Lyons; Timothy J. Albaugh; David R. Carter; Otávio C. Campoe; Rafael A. Rubilar; Matthew Sumnall; Andrew Trlica; Mark V. Corrao; Simerjeet Virk; Rex Lester; Rachel L. Cook (Forest Ecology and Management, 2025)

The Properties of Individual Fire Events Are Essential for Understanding Global Fire Regimes - Adam L. Mahood; Ty Tuff; Megan E. Cattau; Virginia Iglesias; Thomas E. Hanson; Jilmarie Stephens; Nayani Ilangakoon; Maxwell C. Cook; R. Chelsea Nagy; David Barnard; E. Natasha Stavros; Amy DeCastro; et al. (Global Ecology and Biogeography, 2025)
Aim As fire activity changes globally, we need to better understand the spatial and temporal characteristics of the individual events that, when aggregated, constitute fire regimes. Most global studies analyze point detections of burned area, without delineating or considering the properties of individual events. Furthermore, there is a critical need to understand fire patterns within the context of the geopolitical boundaries within which fires are managed. Location Global. Time Period 2003–2020. Major Taxa Studied Fire. Methods We divided 241 countries by Köppen‐Geiger climate classifications and quantified four event‐based fire regime metrics: size, duration, and mean and maximum growth rate; and four area‐based metrics: burned area, number of fires, season length, and season peak. We examined the correlations among fire regime components, and between each fire regime component and climate normals. We quantified temporal trends, and used mixed models to analyze how climate and landcover change were associated with event‐based components of fire regimes. Results Event‐based metrics were weakly correlated with area‐based metrics. Countries with warmer and less variable climates had high burned area, more fire events, longer season lengths and shorter event durations. Countries with high annual temperature range and low precipitation tended to have fewer events but larger fires that were faster‐spreading and occurred later in the year. The growth rate and size of individual fire events are increasing in 18% and 21% of regions we analysed, respectively. Interannual variability in size and growth rate was associated with aridity increases in boreal areas, and landcover changes in arid areas. Main Conclusions Drivers of burned area and fire seasonality are well understood but largely unrelated to the properties of individual events. A more detailed understanding of the spatial and temporal aspects of fire events at broad scales will assist fire management efforts in preparing for a warmer future.

Quantifying above- and belowground biomass improved our understanding of site differences and demonstrated the importance of management decisions in sequestering carbon in Pinus taeda - Timothy J. Albaugh; Chris A. Maier; Otávio C. Campoe; Marshall A. Laviner; Timothy J. Shively; Vitor Aguiar; Kyle R. Peer; David R. Carter; Rachel L. Cook; Rafael A. Rubilar; Thomas R. Fox (Forest Ecology and Management, 2025)

We Need the Largest Experiments on Earth to Achieve Our Climate Targets - Bronson W. Griscom; Susan C. Cook‐Patton; Erin Sills; Kelsey Jack; Thomas W. Crowther; Sebastien Costedoat; Christopher Field; David Hole; Lisa M. McCullough; Subhrendu K. Pattanayak; Sassan Saatchi; Will R. Turner (Global Change Biology, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Evaluating individual tree metrics calculated from unmanned aerial vehicle laser scanning as input to a conventional growth and yield model - Matthew J. Sumnall; David R. Carter; Timothy J. Albaugh; Rachel L. Cook; Otávio C. Campoe; Rafael A. Rubilar (International Journal of Remote Sensing, 2025)

Harmonizing nature’s timescales in ecosystem models - Vivienne P. Groner; Jacob Cook; C. David L. Orme; Priyanga Amarasekare; Edward Comyn-Platt; Taran Rallings; Jaideep Joshi; Robert M. Ewers (Trends in Ecology & Evolution, 2025)

Systemic toxicity after rattlesnake envenomation in patients using angiotensin converting enzyme inhibitors: A North American Snakebite Registry study - A.M. Ruha; M.B. Spyres; R. Culbreth; B. Wolk; C. Hoyte; S. Campleman; Peter Akpunonu; Adam Algren; Alexandra Amaducci; Sukhshant Atti; Connie Aubin; Kevin Baumgartner; et al. (Toxicon, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Crown complementarity rather than crown selection contributes to stem complementarity in genetic mixtures of Pinus taeda L - David R. Carter; Timothy J. Albaugh; Matthew Sumnall; Jake J. Grossman; Otávio C. Campoe; Rachel L. Cook; Rafael A. Rubilar; Chris A. Maier; T. Adam Coates; Julia DeFeo; Grady J. Boyle; Megan Van Spanje (Acta Oecologica, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Evaluating the transferability of airborne laser scanning derived stem size prediction models for Pinus taeda L. stem size estimation to two different locations and acquisition specifications - Matthew J. Sumnall; David R. Carter; Timothy J. Albaugh; Erik Platt; Trevor Host; Rachel L. Cook; Otávio C. Campoe; Rafael A. Rubilar (International Journal of Remote Sensing, 2024)

A framework for studying the effects of offshore wind energy development on birds and bats in the Eastern United States - Kathryn A. Williams; Julia Gulka; Aonghais S. C. P. Cook; Robert H. Diehl; Andrew Farnsworth; Holly Goyert; Cris Hein; Pamela Loring; David Mizrahi; Ib Krag Petersen; Trevor Peterson; Kate McClellan Press; et al. (Frontiers in Marine Science, 2024)
Offshore wind energy development (OWED), while a key strategy for reducing carbon emissions, has potential negative effects to wildlife that should be examined to inform decision making and adaptive management as the industry expands. We present a conceptual framework to guide the long-term study of potential effects to birds and bats from OWED. This framework includes a focus on exposure and vulnerability as key determinants of risk. For birds and bats that are exposed to OWED, there are three main effects of interest that may impact survival and productivity: 1) collision mortality, 2) behavioral responses, including avoidance, displacement, and attraction, and 3) habitat-mediated effects to prey populations. If these OWED effects cause changes in survival and/or breeding success (e.g., fitness), they have the potential for population-level consequences, including changes in population size and structure. Understanding the influence of ecological drivers on exposure and effect parameters can help to disentangle the potential impacts of OWED from other stressors. We use this theoretical framework to summarize existing relevant knowledge and identify current priority research questions (n=22) for the eastern United States, where large-scale development of OWED is primarily in the planning and early construction phase. We also identify recommendations for study design and further prioritization of research topics.

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Need and vision for global medium-resolution Landsat and Sentinel-2 data products - Volker C. Radeloff; David P. Roy; Michael A. Wulder; Martha Anderson; Bruce Cook; Christopher J. Crawford; Mark Friedl; Feng Gao; Noel Gorelick; Matthew Hansen; Sean Healey; Patrick Hostert; et al. (Remote Sensing of Environment, 2024)

Relating social, ecological, and technological vulnerability to future flood exposure at two spatial scales in four U.S. cities - Jason Sauer; Arun Pallathadka; Idowu Ajibade; Marta Berbés-Blázquez; Heejun Chang; Elizabeth M. Cook; Nancy B. Grimm; David M. Iwaniec; Robert Lloyd; Gregory C. Post (Sustainable Cities and Society, 2023)

Modeling forest canopy surface retrievals using very high-resolution spaceborne stereogrammetry: (II) optimizing acquisition configurations - Tiangang Yin; Paul M. Montesano; Bruce D. Cook; Eric Chavanon; Christopher S.R. Neigh; David Shean; Dongju Peng; Nicolas Lauret; Ameni Mkaouar; Omar Regaieg; Zhijun Zhen; Rongjun Qin; et al. (Remote Sensing of Environment, 2023)

Modeling forest canopy surface retrievals using very high-resolution spaceborne stereogrammetry: (I) methods and comparisons with actual data - Tiangang Yin; Paul M. Montesano; Bruce D. Cook; Eric Chavanon; Christopher S.R. Neigh; David Shean; Dongju Peng; Nicolas Lauret; Ameni Mkaouar; Douglas C. Morton; Omar Regaieg; Zhijun Zhen; et al. (Remote Sensing of Environment, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Estimation of individual stem volume and diameter from segmented UAV laser scanning datasets in Pinus taeda L. plantations - Matthew J. Sumnall; Timothy J. Albaugh; David R. Carter; Rachel L. Cook; W. Cully Hession; Otávio C. Campoe; Rafael A. Rubilar; Randolph H. Wynne; Valerie A. Thomas (International Journal of Remote Sensing, 2023)

Mid- and long-chain leaf wax δ2H values in modern plants and lake sediments from mid-latitude North America - Ioana C. Stefanescu; Chandelle Macdonald; Craig S. Cook; David G. Williams; Bryan N. Shuman (Geochimica et Cosmochimica Acta, 2023)

Integrating knowledge on green infrastructure, health and well-being in ageing populations: Principles for research and practice - Matthew Dennis; Adam Barker; Jamie Anderson; Jenna C. Ashton; Gina Cavan; Penny A. Cook; David French; Anna Gilchrist; Philip James; Christopher Phillipson; Konstantinos Tzoulas; C. Philip Wheater; et al. (Ambio, 2023)
Ageing and urbanisation pose significant challenges for public health and urban planning. Ageing populations are at particular risk from hazards arising from urbanisation processes, some of which are in turn exacerbated by climate change. One approach for mitigating the negative effects of urbanisation on ageing populations is the leveraging of the beneficial effects of urban green infrastructure as a public health intervention in the planning process. We assessed the potential of available theoretical frameworks to provide the context for such leverage. This involved active engagement with academics and practitioners specialising in ageing, green infrastructure and health and well-being through a knowledge-brokering approach. We concluded that an integrated and comprehensive framework on the socio-cultural-ecological determinants of health is lacking. To address this, we present a set of principles for overcoming challenges to knowledge integration when working at the intersection of green infrastructure, ageing, health and well-being. Our findings—and the co-production process used to generate them—have wider significance for trans-disciplinary research into the benefits of the natural environment to human health and well-being as well as other complex and interconnected topics associated with global grand challenges.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

The Open-Ocean Gulf of Mexico After Deepwater Horizon: Synthesis of a Decade of Research - Tracey T. Sutton; Rosanna J. Milligan; Kendra Daly; Kevin M. Boswell; April B. Cook; Maëlle Cornic; Tamara Frank; Kaitlin Frasier; Daniel Hahn; Frank Hernandez; John Hildebrand; Chuanmin Hu; et al. (Frontiers in Marine Science, 2022)
The scale of the Deepwater Horizon disaster was and is unprecedented: geographic extent, pollutant amount, countermeasure scope, and of most relevance to this Research Topic issue, range of ecotypes affected. These ecotypes include coastal/nearshore, continental shelf, deep benthic, and open-ocean domains, the last of which is the subject of this synthesis. The open-ocean ecotype comprises ~90% of the volume of the Gulf of Mexico. The exact percentage of this ecotype contaminated with toxins is unknown due to its three-dimensional nature and dynamics, but estimates suggest that the footprint encompassed most of its eastern half. Further, interactions between the water column and the deep benthos may be persistent, making this synthesis one of time (a decade) rather than event conclusion. Here we examine key elements of the open-ocean ecosystem, with emphasis on vulnerability and resilience. Of paramount importance relative to the Gulf nearshore and shelf ecotypes, pre-disaster baseline data were lacking for most of the fauna. In such cases, inferences were drawn from post-disaster assessments. Both phytoplankton and mesozooplankton vulnerabilities were quite high, but resilience appeared equally so. The phytoplankton situation was a bit more complex in that toxin-imposed reductions may have been offset by nutrient injection via high freshwater discharge in 2010. Intermediate trophic levels exhibited population-level depressions, ostensibly due to high vulnerability and low resilience. Apex predator impacts were variable. Certain large epipelagic fishes may have avoided the highest concentrations of hydrocarbons/dispersant, and thus larval abundances returned to pre-disaster levels of variability and abundance within a few years after a steep initial decline. Oceanic cetaceans, particularly shallow-diving stenellid dolphins, did not appear to avoid oiled waters and exhibited strong declines in the northern Gulf. Given that population declines of many open-ocean taxa appear to be ongoing a decade later, we conclude that this largest of Gulf ecosystem components, like its deep-benthic counterpart, is as fragile as it is voluminous. This is particularly concerning given the rapid, and likely irreversible, shift to deeper waters by the US and Mexican oil industries in concert with the higher likelihood of accidents with increasing platform depth.

Effect of varied unmanned aerial vehicle laser scanning pulse density on accurately quantifying forest structure - Matthew J. Sumnall; Timothy J. Albaugh; David R. Carter; Rachel L. Cook; W. Cully Hession; Otávio C. Campoe; Rafael A. Rubilar; Randolph H. Wynne; Valerie A. Thomas (International Journal of Remote Sensing, 2022)

Eucalyptus grandis Response to Calcium Fertilization in Colombia - Zach S Grover; Rachel L Cook; Marcela Zapata; J Byron Urrego; Timothy J Albaugh; Ariel Zelaya; Tomasz Ozyhar; Rafael Rubilar; David R Carter; Otávio C Campoe (Forest Science, 2021)
Calcium (Ca) is a critical plant nutrient typically applied at the time of planting in intensive Eucalyptus plantations in South America. At two sites in Colombia, we examined (1) calcium source by comparing growth after application of 100 kg ha−1 elemental Ca as lime or as pelletized highly reactive calcium fertilizer (HRCF) compared to a no application control, and (2) Ca rate by applying 0, 100, 200, and 400 kg ha−1 elemental Ca as HRCF with the addition of nitrogen, phosphorus, potassium, sulfur, and boron (NPKSB). We assessed height, diameter, and volume after 12 and 24 months. There were no growth differences from Ca source at the 100 kg ha−1 rate. We found increased volume after 24 months at the “Popayan” site with 200 and 400 kg ha−1 Ca HRCF+NPKSB treatments (112 and 113 m3 ha−1, respectively) compared to control (92 m3 ha−1), a 22% increase. In contrast, volume did not differ after 24 months at the “Darien” site, ranging from 114 m3 ha−1 in the 0 kg ha−1 Ca HRCF+NPKSB treatment to 98 m3 ha−1 in the control. Differences in response are likely due to soil characteristics, such as organic matter, emphasizing the importance of identifying site-specific nutrient deficiencies.

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

A 50-Year Retrospective of the Forest Productivity Cooperative in the Southeastern United States: Regionwide Trials - David R Carter; H Lee Allen; Thomas R Fox; Timothy J Albaugh; Rafael A Rubilar; Otávio C Campoe; Rachel L Cook (Journal of Forestry, 2021)
In 2019, the Forest Productivity Cooperative (FPC) celebrated its 50th anniversary. The mission of the FPC is and has been creating innovative solutions to enhance forest productivity and value through the sustainable management of site resources. This industry-government-university partnership has generated seminal research with sweeping implications for increasing productivity throughout the southeastern United States and Latin America. To commemorate this semicentennial, we highlighted some of the pivotal findings in the southeastern United States from the past 50 years derived from our large, regional experiments: regionwide trials.

Epidemiology, Clinical Features, and Management of Texas Coral Snake (Micrurus tener) Envenomations Reported to the North American Snakebite Registry - Spencer Greene; Anne-Michelle Ruha; Sharan Campleman; Jeffrey Brent; Paul Wax; Kim Aldy; Peter Akpunonu; Vikhyat S. Bebarta; Gillian A. Beauchamp; Michael C. Beuhler; Mary Billington; William Boroughf; et al. (Journal of Medical Toxicology, 2021)

A Multidisciplinary Approach to Investigate Deep-Pelagic Ecosystem Dynamics in the Gulf of Mexico Following Deepwater Horizon - April B. Cook; Andrea M. Bernard; Kevin M. Boswell; Heather Bracken-Grissom; Marta D’Elia; Sergio deRada; Cole G. Easson; David English; Ron I. Eytan; Tamara Frank; Chuanmin Hu; Matthew W. Johnston; et al. (Frontiers in Marine Science, 2020)
The pelagic Gulf of Mexico (GoM) is a complex system of dynamic physical oceanography (western boundary current, mesoscale eddies), high biological diversity, and community integration via diel vertical migration and lateral advection. Humans also heavily utilize this system, including its deep-sea components, for resource extraction, shipping, tourism, and other commercial activity. This utilization has had impacts, some with disastrous consequences. The Deepwater Horizon oil spill (DWHOS) occurred at a depth of ∼1500 m (Macondo wellhead), creating a persistent and toxic mixture of hydrocarbons and dispersant in the deep-pelagic (water column below 200 m depth) habitat. In order to assess the impacts of the DWHOS on this habitat, two large-scale research programs, described herein, were designed and executed. These programs, ONSAP and DEEPEND, aimed to quantitatively characterize the oceanic ecosystem of the northern GoM and to establish a time-series with which natural and anthropogenic changes could be detected. The approach was multi-disciplinary in nature and included in situ sampling, acoustic sensing, water column profiling and sampling, satellite remote sensing, AUV sensing, numerical modeling, genetic sequencing, and biogeochemical analyses. The synergy of these methodologies has provided new and unprecedented perspectives of an oceanic ecosystem with respect to composition, connectivity, drivers, and variability.

Effect of blast-related mTBI on the working memory system: a resting state fMRI study - Kathleen F. Pagulayan; Eric C. Petrie; David G. Cook; Rebecca C. Hendrickson; Holly Rau; Melissa Reilly; Cindy Mayer; James S. Meabon; Murray A. Raskind; Elaine R. Peskind; Natalia Kleinhans (Brain Imaging and Behavior, 2020)

Rapid Assessment of Wetland Condition Reflects Amphibian Community Composition - Kari Dupler; Michelle Guidugli-Cook; David R. Brown; Stephen C. Richter (Wetlands, 2020)

Invasive non‐native species likely to threaten biodiversity and ecosystems in the Antarctic Peninsula region - Kevin A. Hughes; Oliver L. Pescott; Jodey Peyton; Tim Adriaens; Elizabeth J. Cottier‐Cook; Gillian Key; Wolfgang Rabitsch; Elena Tricarico; David K. A. Barnes; Naomi Baxter; Mark Belchier; Denise Blake; et al. (Global Change Biology, 2020)
The Antarctic is considered to be a pristine environment relative to other regions of the Earth, but it is increasingly vulnerable to invasions by marine, freshwater and terrestrial non‐native species. The Antarctic Peninsula region (APR), which encompasses the Antarctic Peninsula, South Shetland Islands and South Orkney Islands, is by far the most invaded part of the Antarctica continent. The risk of introduction of invasive non‐native species to the APR is likely to increase with predicted increases in the intensity, diversity and distribution of human activities. Parties that are signatories to the Antarctic Treaty have called for regional assessments of non‐native species risk. In response, taxonomic and Antarctic experts undertook a horizon scanning exercise using expert opinion and consensus approaches to identify the species that are likely to present the highest risk to biodiversity and ecosystems within the APR over the next 10 years. One hundred and three species, currently absent in the APR, were identified as relevant for review, with 13 species identified as presenting a high risk of invading the APR. Marine invertebrates dominated the list of highest risk species, with flowering plants and terrestrial invertebrates also represented; however, vertebrate species were thought unlikely to establish in the APR within the 10 year timeframe. We recommend (a) the further development and application of biosecurity measures by all stakeholders active in the APR, including surveillance for species such as those identified during this horizon scanning exercise, and (b) use of this methodology across the other regions of Antarctica. Without the application of appropriate biosecurity measures, rates of introductions and invasions within the APR are likely to increase, resulting in negative consequences for the biodiversity of the whole continent, as introduced species establish and spread further due to climate change and increasing human activity.

Crown architecture, crown leaf area distribution, and individual tree growth efficiency vary across site, genetic entry, and planting density - Timothy J. Albaugh; Chris A. Maier; Otávio C. Campoe; Marco A. Yáñez; Eric D. Carbaugh; David R. Carter; Rachel L. Cook; Rafael A. Rubilar; Thomas R. Fox (Trees, 2020)

Analysis of recombinant inbred line populations derived from wheat landraces to identify new genes for wheat stem sawfly resistance - Andrea C. Varella; David K. Weaver; Nancy K. Blake; Megan L. Hofland; Hwa-Young Heo; Jason P. Cook; Peggy F. Lamb; Katherine W. Jordan; Eduard Akhunov; Shiaoman Chao; Luther E. Talbert (Theoretical and Applied Genetics, 2019)

Utility of the Compensatory Tracking Task for Objective Differentiation of Hypersomnolence in Depression: A High-Density EEG Investigation - Emily C. Forscher; Michael L. Prairie; Jesse D. Cook; Sydney L. Notermann; David T. Plante (Sleep and Vigilance, 2019)

Developing a list of invasive alien species likely to threaten biodiversity and ecosystems in the European Union - Helen E. Roy; Sven Bacher; Franz Essl; Tim Adriaens; David C. Aldridge; John D. D. Bishop; Tim M. Blackburn; Etienne Branquart; Juliet Brodie; Carles Carboneras; Elizabeth J. Cottier-Cook; Gordon H. Copp; et al. (Global Change Biology, 2019)
The European Union ( EU ) has recently published its first list of invasive alien species ( IAS ) of EU concern to which current legislation must apply. The list comprises species known to pose great threats to biodiversity and needs to be maintained and updated. Horizon scanning is seen as critical to identify the most threatening potential IAS that do not yet occur in Europe to be subsequently risk assessed for future listing. Accordingly, we present a systematic consensus horizon scanning procedure to derive a ranked list of potential IAS likely to arrive, establish, spread and have an impact on biodiversity in the region over the next decade. The approach is unique in the continental scale examined, the breadth of taxonomic groups and environments considered, and the methods and data sources used. International experts were brought together to address five broad thematic groups of potential IAS . For each thematic group the experts first independently assembled lists of potential IAS not yet established in the EU but potentially threatening biodiversity if introduced. Experts were asked to score the species within their thematic group for their separate likelihoods of i) arrival, ii) establishment, iii) spread, and iv) magnitude of the potential negative impact on biodiversity within the EU . Experts then convened for a 2‐day workshop applying consensus methods to compile a ranked list of potential IAS . From an initial working list of 329 species, a list of 66 species not yet established in the EU that were considered to be very high (8 species), high (40 species) or medium (18 species) risk species was derived. Here, we present these species highlighting the potential negative impacts and the most likely biogeographic regions to be affected by these potential IAS.

Under what circumstances does the capture and tagging of wild Atlantic salmon Salmo salar smolts affect probability of return as adults? - William D. Riley; Anton T. Ibbotson; Stephen D. Gregory; Ian C. Russell; Rasmus B. Lauridsen; William R. C. Beaumont; Alastair C. Cook; David L. Maxwell (Journal of Fish Biology, 2018)
Adult return rates for wild Atlantic salmon Salmo salar smolts captured in a rotary screw trap and tagged with coded wire (CW) tags were compared with a control group, using detections from passive integrated transponder (PIT) antennae systems over 7 years in a small chalk stream in southern England, U.K. Compared with control smolts, capture and CW‐tagging of experimental smolts affected detected return rates only under certain conditions, with a decreased return probability for smolts caught and tagged following mild winter river temperature anomalies and during the night. Similarly, analysis of the experimental smolts revealed that capture and CW‐tagging following mild winters decreased their probability of return as adults. There were also marginal positive effects of length at PIT‐tagging as parr and length at CW‐tagging as smolts, on individual probability of return as adult. The results support the hypothesis that the effect of procedures involving the capture and tagging of migrating wild S. salar smolts will vary with the circumstances under which they are performed. The implications of the findings are considered in the context of ongoing investigations to derive and report marine return rates for S. salar in support of national and international stock assessments and in developing best practice.

Field-based assessment of wetland condition, wetland extent, and the National Wetlands Inventory in Kentucky, USA - Michelle Guidugli-Cook; Stephen C. Richter; Barbara J. Scott; David R. Brown (Wetlands Ecology and Management, 2017)

Characterization of resistance to the wheat stem sawfly in spring wheat landrace accessions from targeted geographic regions of the world - Andrea C. Varella; David K. Weaver; Jason P. Cook; Nancy K. Blake; Megan L. Hofland; Peggy F. Lamb; Luther E. Talbert (Euphytica, 2017)

Erratum to: Sex-specific macronutrient foraging strategies in a highly successful marine predator: the Australasian gannet - Gabriel E. Machovsky-Capuska; Alistair M. Senior; Emily C. Benn; Alice H. Tait; Rob Schuckard; Karen A. Stockin; Willie Cook; Mike Ogle; Katherine Barna; David Melville; Belinda Wright; Cameron Purvin; et al. (Marine Biology, 2016)

Sex-specific macronutrient foraging strategies in a highly successful marine predator: the Australasian gannet - Gabriel E. Machovsky-Capuska; Alistair M. Senior; Emily C. Benn; Alice H. Tait; Rob Schuckard; Karen A. Stockin; Willie Cook; Mike Ogle; Katherine Barna; David Melville; Belinda Wright; Cameron Purvin; et al. (Marine Biology, 2016)

A bio-economic ‘war game’ model to simulate plant disease incursions and test response strategies at the landscape scale - David C. Cook; Jean-Philippe Aurambout; Oscar N. Villalta; Shuang Liu; Jacqueline Edwards; Savi Maharaj (Food Security, 2016)

Potential Economic Impact of Panama Disease (Tropical Race 4) on the Australian Banana Industry - David C Cook; Andrew S Taylor; Rachel A Meldrum; André Drenth (Journal of Plant Diseases and Protection, 2015)

Improving treatment strategies for patients with metastatic castrate resistant prostate cancer through personalized computational modeling - Jill Gallaher; Leah M. Cook; Shilpa Gupta; Arturo Araujo; Jasreman Dhillon; Jong Y. Park; Jacob G. Scott; Julio Pow-Sang; David Basanta; Conor C. Lynch (Clinical & Experimental Metastasis, 2014)

Horizon scanning for invasive alien species with the potential to threaten biodiversity in Great Britain - Helen E. Roy; Jodey Peyton; David C. Aldridge; Tristan Bantock; Tim M. Blackburn; Robert Britton; Paul Clark; Elizabeth Cook; Katharina Dehnen‐Schmutz; Trevor Dines; Michael Dobson; François Edwards; et al. (Global Change Biology, 2014)
Invasive alien species ( IAS ) are considered one of the greatest threats to biodiversity, particularly through their interactions with other drivers of change. Horizon scanning, the systematic examination of future potential threats and opportunities, leading to prioritization of IAS threats is seen as an essential component of IAS management. Our aim was to consider IAS that were likely to impact on native biodiversity but were not yet established in the wild in Great Britain. To achieve this, we developed an approach which coupled consensus methods (which have previously been used for collaboratively identifying priorities in other contexts) with rapid risk assessment. The process involved two distinct phases: Preliminary consultation with experts within five groups (plants, terrestrial invertebrates, freshwater invertebrates, vertebrates and marine species) to derive ranked lists of potential IAS. Consensus‐building across expert groups to compile and rank the entire list of potential IAS. Five hundred and ninety‐one species not native to Great Britain were considered. Ninety‐three of these species were agreed to constitute at least a medium risk (based on score and consensus) with respect to them arriving, establishing and posing a threat to native biodiversity. The quagga mussel, Dreissena rostriformis bugensis , received maximum scores for risk of arrival, establishment and impact; following discussions the unanimous consensus was to rank it in the top position. A further 29 species were considered to constitute a high risk and were grouped according to their ranked risk. The remaining 63 species were considered as medium risk, and included in an unranked long list. The information collated through this novel extension of the consensus method for horizon scanning provides evidence for underpinning and prioritizing management both for the species and, perhaps more importantly, their pathways of arrival. Although our study focused on Great Britain, we suggest that the methods adopted are applicable globally.

Foraging behaviour and habitat use of chick-rearing Australasian Gannets in New Zealand - Gabriel E. Machovsky-Capuska; Mark E. Hauber; Mariela Dassis; Eric Libby; Martin C. Wikelski; Rob Schuckard; David S. Melville; Willie Cook; Michelle Houston; David Raubenheimer (Journal of Ornithology, 2014)

A novel approach of homozygous haplotype sharing identifies candidate genes in autism spectrum disorder - Jillian P. Casey; Tiago Magalhaes; Judith M. Conroy; Regina Regan; Naisha Shah; Richard Anney; Denis C. Shields; Brett S. Abrahams; Joana Almeida; Elena Bacchelli; Anthony J. Bailey; Gillian Baird; et al. (Human Genetics, 2012)

Haplotype structure in Ashkenazi Jewish BRCA1 and BRCA2 mutation carriers - Kate M. Im; Tomas Kirchhoff; Xianshu Wang; Todd Green; Clement Y. Chow; Joseph Vijai; Joshua Korn; Mia M. Gaudet; Zachary Fredericksen; V. Shane Pankratz; Candace Guiducci; Andrew Crenshaw; et al. (Human Genetics, 2011)

Prioritising biosecurity investment between agricultural and environmental systems - David C. Cook; Rob W. Fraser; Jeffrey K. Waage; Matthew B. Thomas (Journal of Consumer Protection and Food Safety, 2011)

Mitochondrial DNA reveals multiple Northern Hemisphere introductions of Caprella mutica (Crustacea, Amphipoda) - GAIL V. ASHTON; MARK I. STEVENS; MARK C. HART; DAVID H. GREEN; MICHAEL T. BURROWS; ELIZABETH J. COOK; KATE J. WILLIS (Molecular Ecology, 2008)
Caprella mutica (Crustacea, Amphipoda) has been widely introduced to non‐native regions in the last 40 years. Its native habitat is sub‐boreal northeast Asia, but in the Northern Hemisphere, it is now found on both coasts of North America, and North Atlantic coastlines of Europe. Direct sequencing of mitochondrial DNA (cytochrome c oxidase subunit I gene) was used to compare genetic variation in native and non‐native populations of C. mutica . These data were used to investigate the invasion history of C. mutica and to test potential source populations in Japan. High diversity (31 haplotypes from 49 individuals), but no phylogeographical structure, was identified in four populations in the putative native range. In contrast, non‐native populations showed reduced genetic diversity (7 haplotypes from 249 individuals) and informative phylogeographical structure. Grouping of C. mutica populations into native, east Pacific, and Atlantic groups explained the most among‐region variation (59%). This indicates independent introduction pathways for C. mutica to the Pacific and Atlantic coasts of North America. Two dominant haplotypes were identified in eastern and western Atlantic coastal populations, indicating several dispersal routes within the Atlantic. The analysis indicated that several introductions from multiple sources were likely to be responsible for the observed global distribution of C. mutica , but the pathways were least well defined among the Atlantic populations. The four sampled populations of C. mutica in Japan could not be identified as the direct source of the non‐native populations examined in this study. The high diversity within the Japan populations indicates that the native range needs to be assessed at a far greater scale, both within and among populations, to accurately assess the source of the global spread of C. mutica .

Enhanced cell surface CD44 variant (v6, v9) expression by osteopontin in breast cancer epithelial cells facilitates tumor cell migration: Novel post-transcriptional, post-translational regulation - Subarna A. Khan; Amy C. Cook; Maya Kappil; Ursula Günthert; Ann F. Chambers; Alan B. Tuck; David T. Denhardt (Clinical & Experimental Metastasis, 2005)

Temporal resolution of the Florida manatee (Trichechus manatus latirostris) auditory system - David A. Mann; Debborah E. Colbert; Joseph C. Gaspard; Brandon M. Casper; Mandy L. H. Cook; Roger L. Reep; Gordon B. Bauer (Journal of Comparative Physiology A, 2005)

Growth, loss, and vertical distribution of Pinus radiata fine roots growing at ambient and elevated CO 2 concentration - Stephen M. Thomas; David Whitehead; JefF. B. Reid; Freeman J. Cook; JohN. A. Adams; AlaN. C. Leckie (Global Change Biology, 1999)
Increased below‐ground carbon allocation in forest ecosystems is a likely consequence of rising atmospheric CO 2 concentration. If this results in changes to fine root growth, turnover and distribution long‐term soil carbon cycling and storage could be altered. Bi‐weekly measurements were made to determine the dynamics and distribution of fine roots ( Pinus radiata trees growing at ambient (350 μmol mol –1 ) and elevated (650 μmol mol –1 ) CO 2 concentration in large open‐top chambers. Measurements were made using minirhizotrons installed horizontally at depths of 0.1, 0.3, 0.5 and 0.9 m. During the first year, at a depth of 0.3 m, the increase in relative growth rate of roots occurred 6 weeks earlier in the elevated CO 2 treatment and the maximum rate was reached 10 weeks earlier than for trees in the ambient treatment. After 2 years, cumulative fine root growth ( P t ) was 36% greater for trees growing at elevated CO 2 than at ambient CO 2 concentration, although this difference was not significant. A model of root growth driven by daily soil temperature accounted for between 43 and 99% of root growth variability. Total root loss ( L t ) was 9% in the ambient and 14% in the elevated CO 2 treatment, although this difference was not significant. Root loss was greatest at 0.3 m. In the first year, 62% of fine roots grown between mid‐summer and late‐autumn disappeared within a year in the elevated CO 2 treatment, but only 18% in the ambient CO 2 treatment ( P L t to time accounted for between 74 and 99% of the variability. Root cohort half‐lives were 951 d for the ambient and 333 d for the elevated treatment. Root length density decreased exponentially with depth in both treatments, but relatively more fine roots grown in the elevated CO 2 treatment tended to occur deeper in the soil profile.

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)